(untitled) (Prassi Ecdotiche della Modernità Letteraria, 2021)
Bernard (formerly Bernhard) Berenson published his first book, The Venetian Painter of the Renaissance, in 1894. The book was provided with an index of the artists (the «lists»), according to the attributions of their paintings given by Berenson. Its success led to a large number of editions and reissues in the next ten years (at least until 1914). In this essay I try to analyse how and when the author of the book modified these famous lists by making changes (e.g. in the attributions) often ignored by the XXth century art historians who have not always taken into account the variants.